Efektivitas Penggunaan Media Bolding Terhadap Keterampilan Menulis Cerpen Murid Kelas V SD Inpres Kampung Parang Kecamatan Eremerasa Kabupaten Bantaeng - Sartika Defianty; Abd. Munir Kondongan; Ummu Khaltsum (Journal Innovation In Education, 2023)
The main problem in this research is the lack of short story writing skills in class V students at SD Inpres Kampung Parang, Eremerasa District, Bantaeng Regency. So the researchers used Bolding media (rolling balls). This research aims to determine the effectiveness of Bolding media (rolling balls) on the short story writing skills of class V students at SD Inpres Kampung Parang, Eremerasa District, Bantaeng Regency. The type of research used is an experiment in the form of Pre-Experimental Design. The data source in this research was 15 class V students at SD Inpres Kampung Parang, Eremerasa District, Bantaeng Regency. Data collection was carried out using the results of the assessment of short story writing skills. The data obtained was then analyzed using statistical analysis techniques, namely descriptive statistics and inferential statistics. After analyzing the data, researchers found that student learning outcomes before using Bolding (rolling ball) learning media were relatively low, namely the average score of the Pre-test results was 58 .33, then the average value of the Post-test results is 85.67. After obtaining tCount 9.223 and tTable 2.14479, we get tCount > tTable or 9.223>2.14479. Based on the results of tCount and tTable, it can be said that H0 is rejected and H1 is accepted. This means that the use of Bolding (rolling ball) learning media is effective on short story writing skills for class V elementary school. Presidential Instruction for Parang Village, Eremerasa District, Bantaeng Regency.